Promotion of Territorial Product in Territorial Marketing - O.V. Yakushevska (Економіка, управління та адміністрування)
The promotion of the territorial product is aimed at increasing the attractiveness of the territory as a place of residence or activity. The purpose of this article is to plan and organize the promotion of a territorial product in territorial marketing and determine its role in shaping the attractiveness of the territory.